Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x^2-2x+3\right)\left(\frac{1}{2x}-5\right)\)
\(=\frac{x^2}{2x}-5x^2-\frac{2x}{2x}+10x+\frac{3}{2x}-15\)
\(=\frac{x^2}{2x}-5x^2-16+10x+\frac{3}{2x}\)
\(=-5x^2+\frac{x^2}{2x}+\frac{20x^2}{2x}+\frac{3}{2x}-16\)
\(=-5x^2+\frac{x^2+20x+3}{2x}-16\)
học tốt
(x^2-2x+3)(1/2x-5)=1/2x^3-5x^2-x^2+10x+3/2x-15=1/2x^3-6x^2+11,5x-15
CHI GIẢI CHO NÈ
A=\(\frac{\left(x-1\right)^2}{\left(x-1\right)\left(x-3\right)}=\frac{x-1}{x-3}\)
de A <1 \(\Leftrightarrow\frac{x-1}{x-3}< 1\Leftrightarrow\frac{x-1}{x-3}-1< 0\)
\(\Leftrightarrow\frac{2}{x-3}< 0\Leftrightarrow x-3< 0\Leftrightarrow x< 3\)
\(\left(x-4\right)^2=\left(2x+1\right)^2\)
\(\Leftrightarrow\left(x-4\right)^2-\left(2x+1\right)^2=0\)
\(\Leftrightarrow\left(x-4-2x-1\right)\left(x-4+2x+1\right)=0\)
\(\Leftrightarrow\left(x-5\right)\left(3x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\3x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\3\left(x-1\right)=0\end{cases}}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=5\\x-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\x=1\end{cases}}}\)
\(A=x^3-8-\left(x^3+3x^2+3x+1\right)+3\left(x^2-1\right)\)
\(=x^3-8-x^3-3x^2-3x-1+3x^2-3\)
\(=\left(x^3-x^3\right)+\left(-3x^2+3x^2\right)-3x-8-3\)
\(=-3x-11\)
\(x^{n-1}\left(x+y\right)-y\left(x^{n-1}+y^{n-1}\right)\)
\(=x^{n-1}.x+x^{n-1}.y-y.x^{n-1}-y.y^{n-1}\)
\(=x^{n-1+1}+x^{n-1}y-x^{n-1}y-y^{n-1+1}=x^n-y^n\)
1)M=3x(2x-5y)+(3x-y)(-2x)-1/2(2-26xy)
=-1
2)
a)7x(x-2)-5(x-1)=21x^2-14x^2+3
<=>7x2-19x+5=7x2+3
<=>-19x=-2
<=>x=\(\frac{2}{19}\)
x + 1 = 2
x = 2 - 1
x = 1
@Bảo
#Cafe